1990
DOI: 10.4319/lo.1990.35.2.0424
|View full text |Cite
|
Sign up to set email alerts
|

Rapid ammonium cycling and concentration‐dependent partitioning of ammonium and phosphate: Implications for carbon transfer in planktonic communities

Abstract: Abstract-A short-lived radioactive isotope of nitrogen (13N, half-life = 10 min) of very high specific activity (Z 100 mCi pmol-I) was used to study NH,+ uptake at near-ambient conccntrations in natural planktonic communities. The turnover times of the dissolved NH,+ pool in Long Island Sound ranged, from tens of hours between April and early June to a fraction of an hour between mid-June and late July. The NH,+ turnover time was also rapid in a nearby eutrophic lake. Up to 50% of the ambient NH,+ flux into pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 11 publications
9
56
0
Order By: Relevance
“…In contrast, phytoplankton are expected to sequester an increasing fraction of available nutrients with increasing trophic state as a result of their larger cell size (Cotner and Biddanda 2002). Several studies have demonstrated that the ability of phytoplankton to take up P and accumulate higher intercellular P levels is either comparable (Vadstein et al 1989) or superior to the ability of bacteria (Suttle et al 1990;Cotner and Wetzel 1992;Thingstad et al 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, phytoplankton are expected to sequester an increasing fraction of available nutrients with increasing trophic state as a result of their larger cell size (Cotner and Biddanda 2002). Several studies have demonstrated that the ability of phytoplankton to take up P and accumulate higher intercellular P levels is either comparable (Vadstein et al 1989) or superior to the ability of bacteria (Suttle et al 1990;Cotner and Wetzel 1992;Thingstad et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Irradiance level, Chl a, and DOC concentrations and planktonic community respiration (CR), bacterial respiration (BR), bacterial contribution to planktonic community respiration (BR : CR), and phytoplankton respiration (PR) for the experimental systems studied in the three light-nutrient interaction experiments. quire an increased fraction of the available nutrients as nutrient availability increases (Suttle et al 1987;Cotner and Biddanda 2002). Under such conditions, the nutrient uptake capacity of small bacterial cells is likely to become saturated.…”
Section: Light-nutrient Interaction Experiments-skaneatelesmentioning
confidence: 99%
“…In the oligotrophic oceans the extreme scarcity of organisms leads to much longer turnover times. Suttle et al (1990) suggested that values of 2-5 h indicated P deficiency in the Sargasso Sea. Based on the supporting data we have, we propose that values up to 7 h indicate P deficiency in the eastern Mediterranean.…”
Section: Resultsmentioning
confidence: 99%
“…Suttle et al 1990). In our study, bacterial-size particles (cl pm) dominated the cycling of P in the upper mixed layer of P-deficient areas of the eastern Mediterranean, accounting for 60-85% of P uptake (Table 2, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions (i.e., nitrogen or phosphorus limitation) can create situations where heterotrophic prokaryotes will compete with phytoplankton for dissolved inorganic nutrients available in the surrounding water. Indeed, laboratory experiments have indicated that bacteria can compete effectively with primary producers for NO , NH or PO under these circumstances Ϫ ϩ Ϫ 3 3 4 4 (Currie and Kalff 1984;Bratbak and Thingstad 1985;Suttle et al 1990). Given this ability, one recent survey indicated that the number of field studies demonstrating the uptake of inorganic nitrogen or phosphorus by bacteria has increased as the ecological consequences of this behavior have been recognized by the scientific community (Kirchman 1994).…”
mentioning
confidence: 99%